Small Business Systemization and Growth Strategy for Erik Kaktus Green Souvenir (CV Karya Bumi Lestari) - Ariyanto, Erik; Larso, Dwi (The Indonesian Journal of Business Administration, 2015)
Abtract.In 2013 there were 56.5 million SMEs in Indonesia and accounts for 90% of economic growth in Indonesia. One of the micro small and medium businesses located in Lembang, Bandung is Erik Kaktus (EK) Green Souvenir, which has been established since 2008. EK Green Souvenir is specializing in producing souvenirs and merchandising that made from live plants such as cacti and succulent. The business issues faced by the company are the company is still small scale has not developed into midle scale morover large scale, in addition the company also faces stiff competition from followers. Dealing with the business issues, the company should survive and beat the competition through implementing effective business strategy. With qualitatif research method including literature review, observation, discussion and interview then the internal and external situation analysis was made. Internal analysis of the company using Company Resources Analysis which gives results that company has lack in human resources, operations and database management system and Five C Analysis which gives results that company marketing activities still not optimized. External company analysis use Five Force Analysis shows that the eco-creative market product is still promising and great opportunity to develop. From both situation analysis Business Model Canvas analysis has made, which gives results that company need to enhance the existing Business Model. The results of the analysis then to be made SWOT analysis and root cause problem. The research generates business solution that is to make systematization of business in the marketing, operations, finances and human resources sector. While other solution is to create a strategy for business growth in the market penetration, market development, product development and diversification sector. Implementation of business solutions starting from the construction of Lembang workshop that will become the core activity thus supporting the systematization business processes and business growth by implementing good managerial and sustainable production systems. Keywords: micro small and medium enterprises, cactus and succulent souvenirs, business systematization, growth strategy.In 2013 there were 56.5 million SMEs in Indonesia and accounts for 90% of economic growth in Indonesia. One of the micro small and medium businesses located in Lembang, Bandung is Erik Kaktus (EK) Green Souvenir, which has been established since 2008. EK Green Souvenir is specializing in producing souvenirs and merchandising that made from live plants such as cacti and succulent. The business issues faced by the company are the company is still small scale has not developed into midle scale morover large scale, in addition the company also faces stiff competition from followers. Dealing with the business issues, the company should survive and beat the competition through implementing effective business strategy. With qualitatif research method including literature review, observation, discussion and interview then the internal and external situation analysis was made. Internal analysis of the company using Company Resources Analysis which gives results that company has lack in human resources, operations and database management system and Five C Analysis which gives results that company marketing activities still not optimized. External company analysis use Five Force Analysis shows that the eco-creative market product is still promising and great opportunity to develop. From both situation analysis Business Model Canvas analysis has made, which gives results that company need to enhance the existing Business Model. The results of the analysis then to be made SWOT analysis and root cause problem. The research generates business solution that is to make systematization of business in the marketing, operations, finances and human resources sector. While other solution is to create a strategy for business growth in the market penetration, market development, product development and diversification sector. Implementation of business solutions starting from the construction of Lembang workshop that will become the core activity thus supporting the systematization business processes and business growth by implementing good managerial and sustainable production systems. Keywords: micro small and medium enterprises, cactus and succulent souvenirs, business systematization, growth strategy.